Static respiratory compliance in the newborn. III: Early changes after exogenous surfactant treatment. - Stenson, B J (1994)
Static respiratory system compliance (Crs) was measured by a single breath passive expiratory flow technique in 73 newborn infants treated with exogenous surfactant. The first 39 received Curosurf, a natural porcine surfactant. The other 34 received Exosurf Neonatal, a synthetic surfactant. All had a diagnosis of respiratory distress syndrome with an arterial/alveolar oxygen ratio < 0.22. Static Crs and arterial blood gases were measured shortly before, and at three and 12 hours after the first dose of surfactant. In 32 infants treated with Curosurf with initial static Crs < 1.8 ml/cm H2O/m body length, which is consistent with surfactant deficiency, static Crs improved by 18% at three hours and by 39% at 12 hours along with a median reduction in fractional inspired oxygen (FIO2) at three hours by 0.32. In 26 infants treated with Exosurf with initial Crs < 1.8 ml/cm H2O/m, Crs did not improve three and 12 hours after treatment and oxygenation improved less than after Curosurf, with a median reduction in FIO2 at three hours of 0.11. Fifteen of the 73 (21%) infants had initial static Crs of > or = 1.8 ml/cm H2O/m, not consistent with surfactant deficiency. Thirteen of these 15 infants showed a fall in static Crs after surfactant treatment, raising the question whether exogenous surfactant did them more harm than good. Initial static Crs and surfactant type both appear to determine the early response to the first dose of surfactant. Only a considerably larger, randomised study can show which surfactant is more effective in reducing adverse clinical outcome.